A HISTOLOGIC STUDY OF CARBIMAZOLE-INDUCED HYPERPLASIA OF ADENOHYPOPHYSIS WITH PROTECTIVE ROLE OF THYROXINE IN MALE ALBINO RATS - Khalida Perveen; Naheed Khan; Muhammad Rafique; Syed Sami Ullah; Anjum Naqvi (Journal of the Dow University of Health Sciences, 2009)
O bjective: To assess the frequency and degree o f pituitary hyperplasia in albino rats made hypothyroid by Carbimazole, and the association o f severity of pituitary enlargement, and the response to treatment with throxine. To determine the microscopic changes occurring in Beta basophil cells (Thyroid stimulating hormone & Adreno corticotrophin hormone producing cells) o f Anterior Pituitary gland by giving an antithyroid drug, Carbimazole and Carbimazol plus Thyroxin on Anterior pituitary glands o f male albino rats with increasing time period. Design Experimental study Place: Anatomy Department, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre Karachi.